Effect of copper incorporated into titanium (cp-Ti) and its alloys (Ti-6Al-4V) and its promising antibacterial effect: a systematic review - Cícero Andrade Sigilião Celles; Andréa Cândido dos Reis (Dentistry Review)
The incorporation of copper (Cu) into titanium (cp-Ti) and its alloys (Ti-6Al-4V) for the manufacture of biomaterials has been a much-studied area since the element has an effective antibacterial capacity against bacteria commonly present in the oral cavity. These changes open the way to more effective, promoting better health outcomes and improving rehabilitation prognosis. This review aimed to answer the question: Does the incorporation of Cu into Ti and its alloys significantly enhance the antibacterial effect, including biofilm inhibition and bacterial viability reduction, compared to pure titanium or copper-free alloys? The materials and methods were based on the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA 2020) registered in the Open Science Framework (OSF) (osf.io/qdu37). The search strategy was followed by PICOS, and the Joanna Briggs Institute (JBI) tool was used to analyze the risk of bias. Once the search had been carried out, 1187 articles were found. After a thorough reading of titles, abstracts, and then the full text, 11 were included. The addition of Cu to Ti and its alloys has shown promising antibacterial potential, with safe use for the human body, with concentrations of 3 and 5 wt. % showing a promising effect. This systematic review highlights the significant potential of Cu, demonstrated by the various benefits Cu offers to combat peri‑implant pathogenic bacteria. However, it also emphasizes the need for continued research to determine a consensus on the ideal concentration and the most effective incorporation methods, which combine antibacterial and pro-osteogenic behavior.